Estimating deflections of castellated beams using SolidWorks Simulation - Rusyn, Pavlo; Peleshko, Ivan; Yurchenko, Vitalina (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is a castellated beam, in which the large openings in the web have the shape of a regular hexagon. The beam is investigated for the purpose of assessing deflections. Based on a set of experimental studies, the features of the stress-strain state of castellated beams have been defined. The need to take into account the increased deflections of castellated beams due to the openings in the beam web when calculating the deflections of castellated beams at the serviceability limit state verifications has been determined. A comparative analysis of the deflections obtained as a result of the numerical experiment with the deflections of beams determined using the design code technique has been performed. It was established that for verifications of castellated beams at the serviceability limit state, the error in assessing the deflections of a single-span hinged beam loaded with a uniformly distributed transverse load in some cases reaches 20 %. Recommendations have been devised for estimating deflections of castellated beams. According to the proposed recommendations, the error in estimating castellated beam deflections does not exceed 3 % for the range of the beam span to the total height of its cross-section 8.5<L/h<25. The results are valid only for the range of I-section profiles and only for the case of a uniformly distributed load acting on the beam when the compressed beam flange is out of bending plane restrained and the beam web is perforated with large openings in the form of regular hexagons. It is under such conditions that the results could be implemented in practice both at the stage of selecting cross-sections of the studied class of structures and when designing effective ranges of castellated beams